Aggregation and conformance in differentiated service networks a case study. - Guerin, Roch A. (Computer communication review.)
The Differentiated Service (Diff-Serv) architecture [1] advocates a model based on different ?granularity? at network edges and within the network. In particular, core routers are only required to act on a few aggregates that are meant to offer a pre-defined set of service levels. The use of aggregation raises a number of questions for end-to-end services, in particular when crossing domain boundaries where policing actions may be applied. This paper focuses on the impact of such policing actions in the context of individual and the bulk services built on top of the Expedited Forwarding (EF) [7] per-hop-behavior (PHB). The findings of this investigation confirm and quantify the expected need for reshaping at network boundaries, and identify a number of somewhat unexpected behaviors. Recommendations are also made for when reshaping is not available.